KEPUTUSAN PEMBELIAN ONLINE - Farhat, Laila (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Times have changed, technological progress is the cause. Consumers can find what they want at a better price, with good service, with guaranteed quality, with ease, and with interruptions. This is independence, the consumer determines the fate of the company. For them, leaving or being loyal is not a problem. Then it's time for the company to fix itself. This study examines all matters relating to purchasing decisions, especially those that affect dominantly. How customers are influenced to buy a product online, especially for the middle class. To answer that question, a quantitative approach is carried out by asking questions to respondents. The results showed, price is the main factor that influences the purchase. While service is a reinforcing factor in purchasing decisions